Parties to Crime: Development and Comparison - Santoso, Topo (Universitas Muhammadiyah Yogyakarta, 2020)
This article discusses parties to crime which are an important part of substantive criminal law. This concept is related to the involvement of more than one person in a criminal offence. Problems in participation include its definition, forms of participation, timing of implementation and criminal responsibility of the person involved in the participation. The debate over parties to crime has started from its definition since the formulation the Criminal Code is very short and need interpretation and the differences among the forms of participation. This article also discusses the arrangement of participation in several